UJI EFEKTIVITAS RIZOBAKTERI SEBAGAIA GEN ANATGONIS Sclerotium rolfsii PENYEBAB PENYAKIT BUSUK BATANG PADA TANAMAN KACANG TANAH (Arachis hypogea L.) - Dewi, Ni Kadek Desy Andya; Suprapta, Dewa Ngurah; Khalimi, Khamdan (Journal of Agricultural Science and Biotechnology; Vol 8 No 1 (2019), 2019)
Groundnut (Arachis hypogea L.) is one of important commodities in Indonesia, however the production of groundnut is still relatively low which is partly because of the plant disease i.e. stem rot disease caused by Sclerotium rolfsii. Rhizobacteria is one of the solutions to be used as the biological control agent against S. rolfsii. The aim of this study is to know the effectiveness of rhizobacteria to control stem rot disease caused by S. rolfsii. The results the study showed that among 130 isolates of rhizobacteria tested against S. rolfsii, 11 isolates showed inhibitory activity, and among them one isolate, BjTk11 from exposed the highest inhibitory activity (96.09%) against S. rolfsii. On a green house experiment, treatment with formula of isolate BjTk 11 at doses of 5 g, 10 g, 15 g and 20 g per polybag effectively controlled the pre emergence damping off (disease incidence = 0%) while the disease incidence on control was 23.5%. No post emergence damping off symptom was observed on groundnut treatment with formula of isolate BjTk11, while the disease incidence on control was 75%. The number of sclerotia in soil of control was 79/gram of soil which is obviously higher than those of treatments. The mode of action the rhizobacteria isolates BjTk11 in inhibiting the growth of S. rolfsii is through antibiosis where the rhizobacteria produce the antifungal compound Butanedial, R - (-) - 1,2propanediol, 2,3-Butanediol, Isopropyl Alcohol, Acetic acid, anhydride with formic Acid , 2-bromohexane, 4,5-Diamino-6-hydroxypyrimidine, 4H-Pyran-4one, 3-hydroxy-2-methyl and Cyclotrisiloxane, hexamethyl-. The presence of these compounds probably closely related to the inhibitory activity against S. rolfsii.